2005
DOI: 10.1038/sj.ejcn.1602182
|View full text |Cite
|
Sign up to set email alerts
|

Personalized nutrition communication through ICT application: how to overcome the gap between potential effectiveness and reality

Abstract: The potential effectiveness of personalized nutrition communication through the Internet is promising in terms of addressing personal relevance, flexibility, interactive options and amount of people that can be reached. However, little research on the contribution to behaviour change has been done. The MyFood program at Wageningen University aims at providing insight into strategies to implement personalized nutrition communication through interactive tools. In this article we present the framework for researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…• Scenario 2 -Education: "Scientific, interactive multimedia is broadly accepted and intensively used for Public Health education and preventive medicine." [22,23]. • Scenario 3 -Cancer risk: "Target-group specific information and communication technology-assisted preventive medicine is widely used to reduce the individual's cancer risk."…”
Section: Identification Of Future Ict Scenariosmentioning
confidence: 99%
“…• Scenario 2 -Education: "Scientific, interactive multimedia is broadly accepted and intensively used for Public Health education and preventive medicine." [22,23]. • Scenario 3 -Cancer risk: "Target-group specific information and communication technology-assisted preventive medicine is widely used to reduce the individual's cancer risk."…”
Section: Identification Of Future Ict Scenariosmentioning
confidence: 99%
“…The title of the fourth Heelsum workshop (2004) (64,(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96) showed that we were aware that empowering and support were needed for both family doctors and patients. The disease-based evidence in primary care, the individual strategy of change, and the population interface of primary care were central themes in this workshop.…”
Section: International Workhops Of the Heelsum Collaboration On Nutrmentioning
confidence: 99%
“…Therefore, in the Heelsum workshops, research into the development and impact of computer-tailored nutrition education was reviewed (75), as well as the present and future of computer-tailored nutrition education (85), and the challenges and opportunities presented by the Internet for nutrition education (83,94). Personalized nutrition communication through ICT applications can be instrumental in overcoming the gap between potential effectiveness and reality, according to Bouwman et al (95). They stressed the personal factor in nutrition communication (129) and also explored GPs`perspectives on gene-based personalized nutrition advice (130).…”
Section: The Internet and Personalised Nutritionmentioning
confidence: 99%
“…Personalized nutrition is based on a normative assumption of individual responsibility for health (Komduur et al 2009;Bouwman et al 2005). Health and dietary advice have a long history, but it was not until the 1970s that such advice was framed in terms of individual responsibility for health.…”
Section: Individual Responsibility For Health: Value and Abilitymentioning
confidence: 99%